The Effect of Price Perception and Electronic Word of Mouth on the Purchase Intention of Spotify Premium Service in Surabaya City - Daffa’ul Hanif Muhibin; Zumrotul Fitriyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aimed to investigate the effect of price perception and electronic word of mouth on the purchase intention of Spotify Premium services in Surabaya City. This research employed a quantitative method and involved a sample of 90 respondents, determined using Ghozali's sampling guidelines. The population for this study comprised Spotify users in Surabaya City, while the sample was selected through purposive sampling, consisting of respondents who had previously seen offers for Spotify Premium packages. Both primary and secondary data were used in this study. The data analysis technique employed for this research was Partial Least Squares (PLS) with validity tests, reliability tests, and hypothesis tests. The findings of this study revealed a significant and positive effect of price perception on purchase intention. Additionally, the second research result indicated that electronic word of mouth also had a positive and significant effect on purchase intention.